Quality of Life among Breast Cancer Women in a Tertiary Cancer Hospital in Nepal: A Descriptive Cross-sectional Study - Thapa, Sajan; Khoshin, Liza; Jha, Jay Bhushan; Chhetry, Sapana; Sah, Guru Sharan (Nepalese Journal of Cancer, 2026)
Introduction: Breast cancer is the most commonly diagnosed cancer in women worldwide, and improved survival has elevated health-related quality of life as a critical patient-centered outcome. This study was conducted to determine the mean health-related quality of life among breast cancer patients receiving treatment at a tertiary care hospital in Nepal.Methods: A descriptive cross-sectional study was conducted among 230 breast cancer patients attending the outpatient department of medical oncology, enrolled by non-probability convenience sampling. The Quality of Life Instrument; Breast Cancer Patient Version (QoL-BC), a validated 46-item tool across four domains, was used for data collection. Ethical clearance was obtained from the Institutional Review Committee. Point estimate at 95% Confidence Interval was calculated along with mean and standard deviation for continuous data, and frequency and percentages for binary data.Results: The median age of participants was 50 years. Half of the respondents (50.0%) had fair quality of life while the remaining half (50.0%) had poor quality of life (median score: 226.5; possible score: 46–446). Spiritual well-being recorded the highest median percentage score (65.71%), while psychological well-being recorded the lowest (44.09%). Patients in stages III and IV demonstrated poorer quality of life (50.5%) compared to those in stages I and II (47.5%).Conclusions: Half of the breast cancer patients had poor overall quality of life. Psychological well-being was the most severely impaired domain, while spiritual well-being was relatively preserved, suggesting an important role of spiritual belief in coping. Holistic care addressing all dimensions of quality of life is essential for this population.